Konservasi Hutan Partisipatif Melalui REDD+ (Studi Kasus Kalimantan Tengah Sebagai Provinsi Percontohan REDD+) - Dian Agung Wicaksono; Ananda Prima Yurista (Jurnal Wilayah dan Lingkungan, 2013)
One of mitigating climate change is through REDD+ (Reducing Emissions from Deforestation and Forest Degradation). REDD+ mechanism chosen as an alternative that offers a new concept of forest conservation with economic incentives on the amount of carbon that can be kept in line with a forest or peatland sustainability. Central Kalimantan province to initiate the implementation of REDD+ schemes designated as the pilot province for REDD+ implementation in Indonesia. With the implementation of REDD+ is expected to be the frontline in maintaining forest conservation. That way, the benefits instead of the forests, but also the empowerment of forest communities.